COMPUTATIONAL STUDY OF AERODYNAMIC CHARACTERISTICS OF SINGLE-ROTOR HELICOPTER TAIL ROTOR UNDER THE INFLUENCE OF VORTICAL WAKE OF MAIN ROTOR AT THE HOVER WITH CROSSWIND - Yu. M. Ignatkin; P. V. Makeev; A. I. Shomov; V. A. Ivchin (Научный вестник МГТУ ГА)
For single-rotor helicopters there are special flight modes, when tail rotor (TR) is under significant inductive influence of vortical wake of main rotor (MR). Inductive influence of vortical wake of MR can provoke essential changes in flowing of TR and its aerodynamic characteristics comparing to isolated rotor. In this case increase of tail rotor pitch, necessary for helicopter controlling, is possible.The article contains computational modelling of TR work with vortical wake of MR at the example of MIL Mi-171 helicopter. The modelling has been made on the base of non-linear blade (free wake) vortical model of rotor, produced at Helicopter Design Department of MAI.Helicopter hovering modes with crosswind of various intensity Vz was considered. Thrust-time lationship forisolated TR and TR with vortical wake of MR for equal flight modes was obtained. Flow around the rotors was analyzed, its vortical wake was considered.The results make it possible to clarify the peculiarities of TR work on considered modes and MR influence on its work. It was found out that vortical wake of MR has a more significant impact on TR work with crosswind on the right, when TR falls into vortex ring state mode. Inductive influence of vortical wake of MR leads to vortexring state mode for TR on lower speeds (Vz :: 5 m/s) than in case of isolated work of TR (Vz :: 12,5 m/s). In that case,the required tail rotor pitch has increased by 13% for Vz = 5 m/s. The results of modelling and flight tests led to good agreement.